ONSET LAKTASI TERLAMBAT SERING TERJADI PADA PRIMIPARA - Kesumaningsih, Rr. Fitriyana; Nursanti, Ida (MEDIA ILMU KESEHATAN, 2012)
Background: WHO and UNICEF recommend giving breast milk (ASI) exclusively for 6 months. In 2009, in Indonesia, the coverage of infants who were exclusively breastfed for 6 months was only 34.3%. In Yogyakarta Province, according to the Provincial Health Office of Yogyakarta, the coverage of exclusive breastfeeding in 2010 amounted to 40.57%, whereas the MOH target of achieving exclusive breastfeeding for 6 months was by 80%. There are several factors which hamper exclusive breastfeeding, one of which is the onset of lactation. Delayed onset of lactation can result in inhibition of milk expenditures. Results of research reveal more primiparous mothers delayed onset of lactation than multiparous. Stress during labor and after childbirth can increase levels of cortisol hormone. An increase in cortisol hormone causes decreased levels of oxytocin hormone, which results in the delay of onset of lactation. Objective: To determine the effect of parity on lactation onset in postpartum mothers. Methods: This was an observational study with a prospective cohort design. Research subjects in this study were postpartum mothers. Observations made on the respondents until 72 hours of postpartum period. Analysis of the data in this study used univariable and bivariable analysis. Statistical test used was chi-square with significance level of p <0.05. Results: The results of analysis showed that delayed onset of lactation occurred in 19 postpartum mothers (44%) and 79% were primiparous. Statistical tests with chi-square obtained p-value of 0.00 with a contingency coefficient of 0.35 and Relative Risk of 5.4. Conclusion: Primiparous mothers had a risk of delayed onset of lactation 5.4 times higher than multiparous mothers. Health workers are expected to conduct health education about breastfeeding in postpartum mothers particularly those at risk of delayed onset of lactation (primiparous mothers) Keywords: Onset of lactation, parity, postpartum.